Continuous inline mapping of a dissolved methane plume at a blowout site in the Central North Sea UK using a membrane inlet mass spectrometer – Water column stratification impedes immediate methane release into the atmosphere. (December 2015) - Sommer, Stefan; Schmidt, Mark; Linke, Peter
Abstract: The dissolved methane (CH4 ) plume rising from the crater of the blowout well 22/4b in the Central North Sea was mapped during stratified water column conditions. Geochemical surveys were conducted close to the seafloor at 80.3 m water depth, below the thermocline (61.1 m), and in the mixed surface layer (13.2 m) using membrane inlet mass spectrometry (MIMS) in combination with a towed CTD. Seawater was continuously transferred from the respective depth levels of the CTD to the MIMS by using an inline submersible pump. Close to the seafloor a well-defined CH4 plume extended from the bubble release site ∼460 m towards the southwest. Along this distance CH4 concentrations decreased from a maximum of 7872 nmol l −1 to less than 250 nmol l −1 . Below the thermocline the well-defined CH4 plume shape encountered at the seafloor was distorted and filaments were observed that extended towards the west and southwest in relation to current direction. Where the core of the bubble plume intersected this depth layer, footprints of high CH4 concentrations of up to 17, 900 nmol l −1 were observed. In the mixed surface layer the CH4 distribution with a maximum of up to 3654 nmol l −1 was confined to a small patch of ∼60 m in diameter. The determination of the water column CH4 inventories revealed that CH4 transfer across the thermocline was strongly impeded as only ∼3% of the total water column inventory was located in the mixed surface layer. Best estimate of the CH4 seabed release from the blowout was 1751 tons yr −1 . The fate of the trapped CH4 (∼97%) that does not immediately reach the atmosphere remains speculative. In wintertime, when the water column becomes well mixed as well as during storm events newly released CH4 and the trapped CH4 pool can be transported rapidly to the sea surface and emitted into the atmosphere. Highlights: MIMS used to quantify the dissolved CH4 inventory around a bubble emission site. Conservative estimate of well 22/4b seabed CH4 emission was 1.8 ktons yr −1 . Stratification impedes immediate CH4 release into the atmosphere.